Abridged adapter primers increase the target scope of Hi-Plex. (January 2015) - Nguyen-Dumont, Tú; Hammet, Fleur; Mahmoodi, Maryam; Pope, Bernard J.; Giles, Graham G.; Hopper, Graham G.; Southey, Melissa C.; Park, Daniel J.
Previously, we reported Hi-Plex, an amplicon-based method for targeted massively parallel sequencing capable of generating 60 amplicons simultaneously. In further experiments, however, we found our approach did not scale to higher amplicon numbers. Here, we report a modification to the original Hi-Plex protocol that includes the use of abridged adapter oligonucleotides as universal primers (bridge primers) in the initial PCR mixture. Full-length adapter primers (indexing primers) are included only during latter stages of thermal cycling with concomitant application of elevated annealing temperatures. Using this approach, we demonstrate the application of Hi-Plex across a broad range of amplicon numbers (16-plex, 62-plex, 250-plex, and 1003-plex) while preserving the low amount (25 ng) of input DNA required.